Genetic Engineering Therapy of Stem Cells in Health Law - Syaharani, Aqilla Nur; Wasitaatmadja, Fokky Fuad (Bacarita Law Journal, 2024)
This research aims to reveal legal protection based on health law related to the practice of stem cell therapy as a controversial genetic engineering product in Indonesia. This research used a qualitative method with unstructured interviews that focus on normative-empirical studies, supported by statute approach, case approach and various sources of literature studies. Stem cells therapy shows the potential to cure various types of diseases using genetic engineering technology developed by researchers as a hope for future health. This research found that the role and support of the Government in protecting subjects throughout the practice of stem cells therapy can be seen in the Government's commitment through efforts to improve and set standardized health services in accordance with health law and the 1945 Constitution. The implementation of stem cell therapy in Indonesia is limited to service-based research because the Government does not yet have minimum service standards as guidelines to ensure the safety of the procedure and its success rate. The issues that have been found need to be considered as evaluation material for the Government to immediately establish minimum service standards for stem cell therapy, so that all parties such as hospitals, laboratories, and cell banks have equal standards.